S109. Difference of visual evoked potential study with different types of monitors. (May 2018) - Suh, Bum Chun; Kim, Sang Hoon; Kim, Sang-Beom; Yoon, Won Tae
Abstract : Introduction: Pattern reversal visual evoked potentials (VEPs) study was traditionally done with cathode ray tube (CRT) monitor, however CRT monitors has been rapidly replaced with liquid crystal display (LCD) monitor. So, we wanted to test that LCD monitor can be used for pattern reversal VEPs with short response time instead of CRT monitor. Methods: In 8 normal subjects with 16 eyes, VEPs were done with CRT and response time 1 ms LCD, 5 ms LCD monitors. Latencies of P100 waves and amplitudes of N75-P100 were compared for 3 different monitor groups. Results: Mean latencies of P100 waves were 111.8 ± 6.0 ms for CRT group, 115.8 ± 5.9 ms for 1 ms LCD group and 118.5 ± 6.2 ms for 5 ms LCD group and there was significant difference between latencies of CRT and 5 ms groups ( p  < 0.01, post hoc analysis). Furthermore, latency difference value from CRT group minus LCD group on each subject also showed significant difference between CRT-1 ms LCD and CRT-5 ms LCD ( p  < 0.01). Mean amplitudes of N75-P100 didn't show difference between 3 monitor groups. Conclusion: Latency of P100 wave with LCD monitor with 5 ms response time which is popular in use is longer than that with CRT monitor and LCD monitor with 1 ms response time also showed tendency of delay. These results suggest that the ready-made reference latency value with CRT monitor should not be applied to the reference range with LCD monitor even though short response time.